CRITICAL REVIEW OF THE LEGAL REGULATION OF MICROTRANSACTION ‘GACHA’: A COMPARATIVE STUDY OF ISLAMIC CRIMINAL LAW AND NATIONAL CRIMINAL LAW - Putri, Mutmainna; Rahmawati; Anwar, Alfiansyah; Haq, Islamul; Zulfahmi AR (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2023)
Microtransactions are a type of small-scale financial transaction conducted online. With the advent of the internet, trading transactions no longer require direct interaction between the seller and the buyer, as everything is done through online platforms. One form of microtransaction found in games is gacha. The issue of microtransaction gacha arises due to their inherent gambling elements. However, there is a loophole in current criminal law in Indonesia where no specific regulation governs this issue. This research aims to compare the differences in the legal regulation of microtransaction gacha between national criminal law and Islamic criminal law. The research methodology employed is a comparative method with a literature review approach. The findings of this research indicate that there is no specific regulation in national criminal law that categorizes microtransaction gacha as prohibited acts under the law, whereas, in Islamic criminal law, microtransaction gacha fulfill the elements of gambling and are therefore considered haram (forbidden). Therefore it is important to establish a framework of criminal law that regulates gacha systems to minimize the impacts caused by microtransaction gacha.